Granny Chan in Zen Buddhism: The Historical Deposition and Cultural Manifestation of Buddhist Women’s Zen Wisdom - Liu, Pinghua; Ye, Lizhen (2025)
Zen/Chan Buddhism, as a profound spiritual tradition, has witnessed the emergence and development of a unique phenomenon known as “老婆禪 Granny Chan”, which is deeply intertwined with the spiritual pursuits of Buddhist women throughout history. This proposed research aims to expound and interrogate the hidden treasures of Zen wisdom amassed by these remarkable women, thereby shedding new light on the often-overlooked contributions within the Zen domain. To begin with, by scouring ancient Zen texts, anecdotes, and historical records, we will trace the roots and evolutionary path of “Granny Chan”. These sources are replete with accounts of nameless “grannies” engaging in profound dialogs and encounters with Zen masters. Their sharp insights and spontaneous responses during dharma exchanges, as exemplified in classic koans like “婆子點心 The Granny’s Dimsum” and “婆子燒庵 The Granny Burning the Hermitage”, reveal a depth of understanding that belies their marginalized status in traditional religious narratives. Subsequently, this study will focus on dissecting the distinct ways in which their Zen wisdom was manifested within the cultural context of Zen. Their approach, characterized by simplicity, directness, and a deep connection to life’s realities, not only added a refreshing dimension to Zen teachings but also subtly challenged the male-dominated paradigm prevalent in the religious fields. By highlighting these expressions, we can appreciate how Buddhist women’s insights became an integral part of Zen’s cultural fabric. In the contemporary context, this research holds multiple implications. It serves as a corrective to the historical neglect of Buddhist women’s spiritual achievements, providing a source of inspiration and empowerment for modern female practitioners. Moreover, it prompts a rethinking of gender equality within religious traditions, advocating for a more inclusive and equitable recognition of women’s roles in the Zen community and beyond. Overall, through the exploration of “Granny Chan”, we anticipate contributing to a better understanding of Zen Buddhism’s historical, cultural, and spiritual dimensions, bridging the gender gap and enriching the ongoing discourse on religious wisdom.
Keywords: religious traditions; Gender Equality; Zen wisdom; Buddhist women; Granny Chan (老婆禪); Zen/Chan Buddhism